Field measurements of horizontal forward motion velocities of terrestrial dust devils: Towards a proxy for ambient winds on Mars and Earth - Balme, M.; Pathare, A.; Metzger, S.; Towner, Martin; Lewis, S.; Spiga, A.; Fenton, L.; Renno, N.; Elliot, H.; Saca, F.; Michaels, T.; Russell, P.; et al. (Academic Press, 2012)
Dust devils – convective vortices made visible by the dust and debris they entrain – are common in arid environments and have been observed on Earth and Mars. Martian dust devils have been identified both in images taken at the surface and in remote sensing observations from orbiting spacecraft. Observations from landing craft and orbiting instruments have allowed the dust devil translational forward motion (ground velocity) to be calculated, but it is unclear how these velocities relate to the local ambient wind conditions, for (i) only model wind speeds are generally available for Mars, and (ii) on Earth only anecdotal evidence exists that compares dust devil ground velocity with ambient wind velocity. If dust devil ground velocity can be reliably correlated to the ambient wind regime, observations of dust devils could provide a proxy for wind speed and direction measurements on Mars. Hence, dust devil ground velocities could be used to probe the circulation of the martian boundary layer and help constrain climate models or assess the safety of future landing sites. We present results from a field study of terrestrial dust devils performed in the southwest USA in which we measured dust devil horizontal velocity as a function of ambient wind velocity. We acquired stereo images of more than a 100 active dust devils and recorded multiple size and position measurements for each dust devil. We used these data to calculate dust devil translational velocity. The dust devils were within a study area bounded by 10 m high meteorology towers such that dust devil speed and direction could be correlated with the local ambient wind speed and direction measurements.